The Development of Teaching Model Based on Knowledge Creation Theory of Principles and Techniques in Nursing to Develop the Analytical Thinking Skills of Nursing Students Boromarajonani College of Nursing Suratthani - Chantra, Rungnapa; Thanaroj, Supalak; Rattanamanee, Kittiya; Untaja, Patcharaporn (Journal of The Royal Thai Army Nurses, 2021)
The research study aimed to 1) develop the teaching model of principles and techniques in nursing; 2) develop analytical skills of nursing students Boromarajonani College of Nursing Suratthani. The sample in this research was 95 academic year 2 nursing students. The instruments consisted of 1) instructor’s manual 2) Analytical thinking test of Principles and Techniques in Nursing 3) assessment form for Teaching and Learning Efficiency of Principles and Techniques in Nursing. The data were collected by analytical thinking skills test with descriptive statistics. The study revealed the following results: 1) the model of principles and techniques in nursing to develop analytical skills of nursing students Boromarajonani College of Nursing Suratthani consists of 5 steps which are 1) preparation for learning 2) learning and practice 3) reflection 4) knowledge creation and 5) assessment (Evaluation: E) The result from the teaching and learning according to the said format makes 47.40% of nursing students have analytical skills of courses, principles and techniques in nursing more than 60% of the scores according to weight determination.